Nanopriming using plastic-derived carbon nanomaterials: boosting growth and salt tolerance of pea (Pisum sativum L.) - Liang, Lili (2024)
Seed priming with nanomaterials is a promising strategy to confront current agriculture challenges, such as salt stress, which drastically caused a reduction in crop productivity and quality. In the current study, a valorization pathway for carbon nanomaterials (CNMs) produced from plastics, a commonly available waste stream, was developed by utilizing them as nanopriming agents. Here, carbon dots (CDs) and carbon nanotubes (CNTs) at two concentrations (0.25 and 0.75 mg/mL) and Milli-Q water (control) were adopted for seed priming of pea (Pisum sativum L.). Their impacts on seed germination and seedling growth in the presence and absence of salt stress (200 mM NaCl) were investigated. The results showed that both CNMs efficiently improved seed germination, shoot and root elongation, and biomass accumulation of pea plants by enhancing seed water uptake, root vitality, the photosynthetic process, and total carbohydrate accumulation. They also strengthened the salt tolerance of pea seedlings by activating the antioxidant enzyme system, upregulating proline content, and maintaining membrane integrity. Moreover, CNM priming significantly reduced Na+ accumulation and achieved lower Na+/K+ ratios in pea seedlings to maintain ion homeostasis in plant cells. This study revealed that plastic-derived CNMs could considerably facilitate seed germination, improve seedling growth, and enhance salt tolerance in pea plants, providing viable and sustainable solutions for waste management, agricultural renovation, and salt stress alleviation.